The master’s degree in development practice: a case study of twelve university programs - Clarke, Faith; Gano, Gretchen; Currey, Robin; Alleyne, John (Frontiers in Sustainability, 2024)
Sustainable development is a global priority. However, a lack of research exists on the effectiveness of programs within the ecosystem of programs designed to train sustainable development practitioners. This multi-case case study, possibly among the first to describeanalyze the programsecosystem that trains development practitioners, utilized case study theory and semi-structured interviews with program administrators to describe and analyze sustainable development programs offered by 12 higher education institutions in eight countries with membership in the Global Association of Masters in Development Practice in eight countries. The results revealed five themes or key drivers, and ninenine advantages, and fourXX deficiencies across the programs analyzed. Two drivers were enrollment-focused (admission of students with prior work experience in development and offer of financial support), two were curriculum-focused (incorporation of field work and integration of specific knowledge aspects and skills training in the curricula), and one was institutional attitude (adoption of a culture of flexibility). The most common challenges were impacts from the COVID-19 pandemic. These results provide insights for continuous improvement efforts of program administrators for students in sustainable development. The practical methodology developed can be replicated and adapted for investigation of similar programs and other disciplines in higher education.